Dynamics of cell division - Endow, Sharyn A.; Glover, David M. (Oxford University Press, 1998)
This volume focuses on the structural aspects of cell division, ranging from nuclear envelope breakdown to cytokinesis and partitioning of the cytoplasm. It examines spindle assembly and chromosome behaviour in mitosis and meiosis, centromere and kinetochore structure and regulation, telomeres, the role of centrosomes, and mechanisms by which overall regulation is achieved. The up-to-date reviews of each topic provide perspectives on recent important findings. Each chapter presents models and new ideas that accommodate available information.
Keywords: Cell division.; Cell Division; Cellules -- Division.; SCIENCE -- Life Sciences -- Developmental Biology.; Cell division; Zellzyklus; Regulation; Zellteilung; Aufsatzsammlung; Biologie